Predictive Factors for Well-being of Vietnamese Undergraduate Students and Gratitude Journaling Intervention - Huynh Dieu To Nhu; Nguyen Viet Anh; Vo Nhat Huy (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
The current study investigated the impact of predictive factors on the well-being of undergraduates in Ho Chi Minh City. Those factors were relationship satisfaction, academic achievement satisfaction, and financial well-being. Besides, the study explored the effectiveness of gratitude journaling in increasing students’ well-being. There are two phases in this study, in the first phase, referred to as study 1, a total of 102 undergraduates from twenty-two universities in Ho Chi Minh City were surveyed. After being controlled for individual differences in socio-economic status, the multiple linear regression results showed that satisfaction in the relationship and academic achievement positively predicted overall well-being, while financial well-being did not make a significant contribution. In the second phase, which is study 2, forty-five participants from study 1 agreed to move on to this phase, where they were randomly divided into two groups for a controlled pre and post-experiment. The experimental group practiced self-guided gratitude journaling for seven days. Analysis of covariance assessment was made to evaluate the impact model and the improvement of participants’ well-being before and after the experiment. Results showed that the difference in well-being between the control and experimental group was insignificant and did not come directly from practicing gratitude journaling, but might indicate individual and cultural differences in well-being. Further research on cross-cultural differences and standardized protocol is encouraged. Received 10th February 2024; Revised 15th March 2024; Accepted 5th April 2024